Effect of UV radiation on degradation of durian skin fibre composite - Abd. Rashid, Siti Munirah Salimah; Anuar, Hazleen; Mohd Apandi, Siti Nur E'zzati; Buys, Yose Fachmi (Deer Hill Publications, 2018)
Durian skin fibre (DSF) reinforced high-density polyethylene (HDPE) composite was fabricated by melt-blending and then compression moulded. As DSF is polar and hydrophilic in nature, while HDPE is non-polar and hydrophobic, thus the adhesion between them is low. Therefore, maleic anhydride-grafted-polyethylene (MAPE) was added to enhance the interaction of HDPE and DSF. This paper highlight the effect of MAPE on UV degradation exposure on HDPE/DSF composite. DSF content from 10, 20, 30 and 40 wt% were immersed in water for 70 days. In the absence of MAPE, water absorption increased with DSF loadings. Furthermore, tensile properties of HDPE/DSF composite was degraded after 500, 1000 and 2000 h of UV radiation exposure. Morphological observation under SEM showed that the fibre and matrix became less interacted after exposed to UV radiation. Voids and gaps between HDPE and DSF in the presence of MAPE were reduced as revealed under SEM micrographs. The colour index of the HDPE/DSF composite was increased and became whiter with UV radiation exposure. This showed that MAPE significantly improved the interaction of HDPE/DSF composite.